Substitution between Cars within the Household - Bruno De Borger; Ismir Mulalic; Jan Rouwendal (Tinbergen Institute, 2013)
In this paper we study the demand for car kilometres in two-car households, focusing on the substitution between cars in response to fuel price changes. We use a large sample of detailed Danish data on two-car households to estimate – for each car owned by the household – own and cross-price effects of increases in fuel costs per kilometre. The empirical results show that failure to capture substitution between cars within the household can result in substantial misspecification biases. Ignoring substitution, we estimate fuel price elasticities of –0.81 and -0.65 for the primary and secondary cars, respectively. When we do take into account the substitution effect, these figures reduce to, respectively, -0.32 and -0.45. We further estimate an alternative version of the model to test the hypothesis that substitution in response to higher fuel prices will be predom inantly from the least to the most fuel efficient car, finding partial support for the underlying hypothesis. More importantly, the results of this extended model emphasize the importance of behavioural differences related to the position of the most fuel efficient car in the household, suggesting that households' fuel efficiency choices are related to their price sensitivity.
Keywords: D12; R41; Q41; 330; Fuel efficiency; car use; multiple car ownership; substitution effects; fuel consumption